2018
DOI: 10.3892/mmr.2018.9082
|View full text |Cite
|
Sign up to set email alerts
|

Bushen recipe and its disassembled prescriptions inhibit inflammation of liver injury associated with Concanavalin A through Toll‑like receptor 3/9 signaling pathway

Abstract: The aim of the present study was to explore the effect of Bushen recipe and its disassembled prescriptions on liver injury and chronic hepatitis B. Liver injury was induced in normal and hepatitis B virus (HBV)-transgenic mice through injection of Concanavalin A, followed by treatment with Bushen recipe and its disassembled prescriptions including the Bushen-yang, the Bushen-yin and the QingHua groups as well as the GanYanLing group (positive control). Subsequently, their liver function indexes were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The equivalent dose ratio was obtained between humans and animals based on body surface area. The conversion factor between mouse (20 g) and human (70 kg) is 0.0026 ( Nie et al, 2018 ). At the same time, the content of flavonoids in GPE was 16% by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…The equivalent dose ratio was obtained between humans and animals based on body surface area. The conversion factor between mouse (20 g) and human (70 kg) is 0.0026 ( Nie et al, 2018 ). At the same time, the content of flavonoids in GPE was 16% by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the earliest discovered pattern recognition receptors, TLRs are involved in inflammatory response and NF-κB activation [28,31]. Moreover, Con A stimulates the expression of TLR2, TLR4, and TLR9 and downstream pathways in liver tissue, resulting in the release of numerous proinflammatory factors [12,13].…”
Section: Effect Of Serotonin On Intrahepatic Tlr Signalingmentioning
confidence: 99%
“…As one of the earliest identified pattern recognition receptors (PRRs), toll-like receptors (TLRs) have been widely studied and are involved in the regulation of inflammatory and apoptotic responses [11]. Previous studies have shown that Con A can stimulate the expression of TLRs and downstream pathways in liver tissue, leading to the initiation of inflammatory response [12,13]. After binding ligand, TLRs stimulate nuclear factor kappa B (NF-κB) activation and trigger the release of various inflammatory mediators, such as tumor necrosis-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-17 (IL-17) [11,14].…”
Section: Introductionmentioning
confidence: 99%